2022
DOI: 10.5751/es-12988-270122
|View full text |Cite
|
Sign up to set email alerts
|

Enabling ecosystem services at the neighborhood scale while allowing for urban regrowth: the case of Halle, Germany

Abstract: Cities that begin to regrow after a long period of decline and land abandonment are under pressure to provide comfortable housing conditions in preferred neighborhoods for their residents. On the other hand, these cities should preserve interim green spaces that result from decline because these spaces are a real treasure for densifying cities. Using the case of the city of Halle in post-socialist Eastern Germany, we explore four land use alternatives for neighborhood development close to what might happen: (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…In our study, we documented an average foraging trip duration of 28 min, which is much shorter compared to the average trip duration of B. terrestris foragers observed in other studies at agricultural sites (56 min: Osborne et al, 1999; 46 min: Maurer et al, 2020) as well as urban sites (68 min: Spaethe & Weidenmuller, 2002). Halle (Saale) is a green city (Haase & Wolff, 2022) and thus the high availability of floral resources within the urban sampling locations of our study might be the explanation of the shorter average foraging trips that we observed.…”
Section: Discussionmentioning
confidence: 67%
“…In our study, we documented an average foraging trip duration of 28 min, which is much shorter compared to the average trip duration of B. terrestris foragers observed in other studies at agricultural sites (56 min: Osborne et al, 1999; 46 min: Maurer et al, 2020) as well as urban sites (68 min: Spaethe & Weidenmuller, 2002). Halle (Saale) is a green city (Haase & Wolff, 2022) and thus the high availability of floral resources within the urban sampling locations of our study might be the explanation of the shorter average foraging trips that we observed.…”
Section: Discussionmentioning
confidence: 67%
“…This evidence is not new, as several studies reveal the presence of environmental injustice in the city of Porto (Graça et al, 2018;Hoffimann et al, 2017;Vidal et al, 2021c), which is a trend of the south-European cities (Kabisch et al, 2016;Ribeiro et al, 2017). However, some studies focused on central-European cities, with a similar dimension to Porto, have also identified this uneven distribution of PUGS, namely Brussels (Stessens et al, 2017), Halle (Haase and Wolff, 2022) and Salzburg (Artmann et al, 2019).…”
Section: Radar Charts Legendmentioning
confidence: 94%
“…This network basically consists of large forest patches as well as bigger parks, while the centrally located parks serve as both habitats and relevant connectors for the whole network. Being relevant for recreation and biodiversity, the corresponding parks need to be the subject of follow-up studies on the trade-offs between these two ecosystem services [72,73]. In addition, secondary networks substantially contribute to functional connectivity in other parts of the city for which, in particular, cemeteries, allotment gardens, or green sport facilities play a key role.…”
Section: The Complex Role Of Existing and Revitalised Brownfields For...mentioning
confidence: 99%